The Effect of Total Quality Management Practices on Institutional Performance: An Empirical Analysis Using Saudi Institutional Accreditation Standards - Alanazi, Mohammed (The Arab Journal of Administration, 2022)
Total quality management is a management approach aimed at achieving performance excellence. This approach must be operationalized using a particular framework. In this context, institutional accreditation standards are used as a guide for implementing total quality management by higher education institutions. There is a lack of research indicating the impact of these standards on performance. This study aims to analyze the effect of Saudi institutional accreditation standards (SIAS) on institutional performance. For this purpose, data were collected using a survey questionnaire from 203 administrative and academic managers in Saudi higher education institutions. Research hypotheses were tested using structural equation modeling. The results indicate a largely positive effect of the SIAS on institutional performance. A correlation is observed between the various institutional accreditation practices, while Saudi higher education institutions generally exhibit a positive level of applying SIAS. In addition, several academic and practical recommendations are presented in the context of higher education institutions.